Light Chain Multiple Myeloma: High Serum Free Light Chain Concentrations Portend Renal Damage and Poorer Survival. (1st September 2021) - Jin, Yulan; Savage, Natasha M; Bollag, Roni J; Xu, Hongyan; Singh, Gurmukh
Abstract: Background: Monoclonal immunoglobulins provide an indication of the tumor burden in patients with plasma cell neoplasms. Higher concentrations of serum free light chains in light chain predominant multiple myeloma have been shown to correlate with a poorer outcome. We examined the correlations of serum free light chain concentrations in light chain myelomas with survival, estimated glomerular filtration rate (eGFR) and other clinical and pathological parameters. Methods: Records of patients with light chain multiple myelomas were reviewed. Highest concentration of serum free light chains for each patient were plotted to ascertain an inflection/change point. Survival, eGFR, and other clinical and pathological parameters were compared between the low and high light chain concentration groups. Results: Plotting serum free light chain concentrations revealed an inflection point at a concentration of 455 mg/L apportioning patients in to 2 subgroups: 39 patients with low light chain concentrations and 26 patients with high concentrations. The high concentration group had more unfavorable pathology in bone marrow examination in terms of higher neoplastic plasma cell burden and high-risk cytogenetics. The survival rate and eGFR in the high concentration group were significantly worse than in the low concentration group. Conclusions: As noted for light chain predominant multiple myeloma, high serum free light chain concentration in light chain multiple myelomas are associated with higher renal disease burden and shorter survival. Monitoring of serum free light chain concentrations and customizing treatments to address this parameter are warranted.